1976
DOI: 10.3171/jns.1976.44.1.0012
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord blood flow as affected by changes in systemic arterial blood pressure

Abstract: The authors used the hydrogen clearance method to measure focal spinal cord blood flow (SCBF) in the rhesus monkey over a wide range of mean arterial blood pressures (MAP) in an attempt to test the hypothesis of autoregulation. The MAP was either lowered by bleeding or raised by the intravenous infusion of norepinephrine or angiotensin. The SCBF remained constant and in the normal range with an MAP of 50 to 135 mm Hg, indicating the presence of autoregulation. Below 50 mm Hg, SCBF fell passively with further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(21 citation statements)
references
References 8 publications
0
20
1
Order By: Relevance
“…Below 60 mm Hg, flow decreased with further reductions in blood pressure. Kobrine et al, 32 using hydrogen clearance, also demonstrated that spinal cord blood flow in the white matter remained constant in the range of 50-135 mm Hg, indicating the presence of autoregulation. Similarly, Flohr et al,33 demonstrated with the particle distribution method that autoregulation was in effect between MAP 60-160 mm Hg.…”
Section: Table 2 Cerebral Blood Flow In the Ratmentioning
confidence: 96%
See 1 more Smart Citation
“…Below 60 mm Hg, flow decreased with further reductions in blood pressure. Kobrine et al, 32 using hydrogen clearance, also demonstrated that spinal cord blood flow in the white matter remained constant in the range of 50-135 mm Hg, indicating the presence of autoregulation. Similarly, Flohr et al,33 demonstrated with the particle distribution method that autoregulation was in effect between MAP 60-160 mm Hg.…”
Section: Table 2 Cerebral Blood Flow In the Ratmentioning
confidence: 96%
“…The effects of variations of blood pressure on spinal cord blood flow has been investigated by Kindt,31 Griffiths, 13 Kobrine et al, 32 and Flohr et al 33 Kindt, 31 using a surface flow device which measured qualitative changes only, reported that spinal cord blood flow did not change with systemic blood pressure elevation. Using the Xenon washout curve after direct intraparenchymal spinal cord injection, Griffiths" demonstrated no significant change in white matter flow between 60-150 mm Hg.…”
Section: Table 2 Cerebral Blood Flow In the Ratmentioning
confidence: 99%
“…Spinal cord ischemia is a likely consequence of both local and systemic vascular alterations after severe injury (Tator, 1991(Tator, , 1998Young, 1993). Local vascular alterations include immediate mechanical damage of the microvasculature and focal, post-injury vasospasm, both of which lead to loss of autoregulation of spinal cord blood flow (Guha et al, 1989;Kobrine et al, 1976;Senter and Venes, 1979;Young et al, 1982). Systemic hypotension compounds local spinal cord ischemia by further reducing perfusion, ultimately reducing spinal cord tissue delivery of oxygen (DO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of variations of blood pressure on spinal cord blood flow have been investigated by Kindt [15], Griffiths [11], Kobrine etal. [17], and Flohr etal. [10].…”
Section: Discussionmentioning
confidence: 99%